P010 Maximising departmental income; a quality improvement project for improving HIV testing and coding. (30th June 2016) - Parry, Laura
Abstract : Background: BASHH standards recommend that 97% of 1 st attenders to GUM services should be offered an HIV test to facilitate prompt diagnosis. This standard now features as a key performance indicator (KPI) in contracts where financial penalties are imposed for non-compliance. Aim: 97% of first GUM attendances will be offered an HIV test by August 2015. Methods: Quality improvement (QI) methodology was applied and key drivers were identified: 1) Staff: Timetabled administration sessions and training. 2) Communication: Weekly email reminders to staff regarding coding accuracy. 3) Timing: Timely upload of missed HIV codes by reception. 4) Measurement: Performance recorded/reviewed monthly. Plan-do-study-act cycles (PDSA) were used: PDSA 1: Computerised administration recall system launched resulting in all clinical administration tasks becoming computerised and accessible from any site across the Trust. Standard Operating Procedures (SOP) developed. Team training. PDSA 2: Reception team briefed/delegated task of uploading missed HIV codes. Weekly email reminders sent to staff. PDSA 3: Administration recall SOPs uploaded to intranet. New staff inductions delivered. Results: Prior to introduction of this project only 89% of new attenders were offered an HIV test (May 2014). We have exceeded our aim with 100% offered, avoiding a potential penalty of £19, 165 per month, securing £229, 980 income over the past 12 months. Discussion: Using QI methodology, robust systems can be implemented improving patient care and facilitating meeting KPIs.